Geografia e migrações: o caso dos haitianos no município de São Paulo - Bocci, Diego Segobia (2015)
The dissertation's subject matter is the current standard of recent international migration flows. With this, the overall objectives are to reflect on increasing the amount of people that make up this stream and analyzing the reasons beyond control and migratory violence. As specific objectives, we seek to analyze the existential bases of production and forms of exploitation of its poorest members. The theoretical-methodological structure is based on historical and dialectical materialism, that geography also expressed. In this sense, within the social and space capitalist reality, people who make up the international migration, especially the most deprived of the means of existence, have become commodities, which are marketed in different locations in the world, which globalization has strengthened this reality, since it intensified rooting, global, hegemonic ideology of the ruling class